Penyuluhan Kesiapsiagaan Menghadapi Bencana Gempa Bumi Terhadap Pengetahuan Pemuda di Karang Taruna Pedukuhan Pundong Kabupaten Bantul Yogyakarta - Rahmawati, Nindi; Puspito, Heri; Wulandari, Endah Tri (PANDITA: Interdisciplinary Journal of Public Affairs, 2024)
Indonesia is classified as a country at great risk of experiencing disaster because it is in the ring of fire and where two world plates meet. An earthquake occurred in Yogyakarta on May 27 2006 with a magnitude of 5.9 on the Richter scale, causing many victims of life and property. The Opak River in Potrobayan Hamlet, Srihardono, Pundong was the epicenter of the earthquake. The factor causing many victims and damage during an earthquake is the lack of knowledge and preparedness of the community. Community preparedness can be increased through outreach. This research aims to determine the effect of counseling on preparedness for earthquake disasters on the knowledge of youth in the Srihardono sub-district youth group. Quantitative experimental design one group pretest-posttest was the method the researcher chose. The sample was 52 people determined by simple random sampling. There is an influence of education on preparedness for earthquake disasters on the knowledge of youth in the Srihardono sub-district youth organization with a p value of 0.000.